SIMULATION OF POTENTIAL TEMPERATUR AND WIND VELOCITY TO IDENTIFY GRAVITY WAVES OVER WEST SUMATERA USING WRF-ARW MODEL - AYU PUTRININGRUM (NIM : 12809022); Pembimbing : Dr. Nurjanna Joko Trilaksono ; Noersomadi, M.Si, DYAH
Gravity waves play an important role in the dynamical of atmosphere. It also affect some procceses in Planetary Boundary Layer (PBL). Gravity waves is identified by potential temperatur and vertical wind velocity using Weather Research and Forecasting–Advance Research WRF (WRF-ARW) model with initial and boundary conditions are FNL data at 16-17 March 2008 and three nested domain with the highest horizontal resolution is 3 km. Simulation include two experiments of PBL parameterization, which are Medium Range Forecast (MRF) and Yonsei University (YSU). The phenomenon and characteristics of gravity waves are studied using fourier and wavelet transform’s analysis method. Gravity waves can be well identified using MRF scheme over Sumatera when the convection activity has established. Gravity waves over Sumatera is short period (~2 hour) with 5–50 km horizontal wavelength. The difference character between two experiments is related to the sensitivity of PBL scheme and horizontal grid resolution. In this case, MRF scheme well capture gravity waves phenomenon, while 3 km horizontal resolution can produce shorter wavelength.